1978
DOI: 10.1042/bj1740453
|View full text |Cite
|
Sign up to set email alerts
|

The pH-dependence of sugar-transport and glycolysis in cultured Ehrlich ascites-tumour cells

Abstract: 1. pH-dependence of glycolysis has generally been ascribed to the effects of pH on the activities of glycolytic enzymes. The present study shows that sugar transport is pHdependent in cultured Ehrlich ascites-tumour cells. 2. The rates of glucose consumption, of 3-0-methylglucose transport, and of 2-deoxyglucose transport and phosphorylation increased as linear functions of pH, as the pH ofthe cell culture medium was increased from 6.1 to 8.5. Transport of glucose, as measured in ATP-depleted cells, was pH-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…1). Acidic pH e was reported to inhibit glycolysis via decreased glucose uptake in Ehrlich ascites tumor cells (72) and our data indicate that melanoma cells exposed to acidic pH show signs of glycolysis inhibition because they reduced glucose uptake and lactate release. Similarly, glycolysis inhibition by 2-deoxy-D-glucose was reported to induce cytoprotective autophagy in endothelial and melanoma cells (73,74).…”
Section: Discussionmentioning
confidence: 52%
“…1). Acidic pH e was reported to inhibit glycolysis via decreased glucose uptake in Ehrlich ascites tumor cells (72) and our data indicate that melanoma cells exposed to acidic pH show signs of glycolysis inhibition because they reduced glucose uptake and lactate release. Similarly, glycolysis inhibition by 2-deoxy-D-glucose was reported to induce cytoprotective autophagy in endothelial and melanoma cells (73,74).…”
Section: Discussionmentioning
confidence: 52%
“…Glycolysis is a metabolic pathway involving a complex chain of chemical reactions that produces energy rich molecules (ATP) [47]. Studies by Kaminkas [50] showed that glucose transport and consumption in cultured Ehrlich ascites-tumour cells are pH dependent. Decreasing pH i is found to decrease the rate of glucose consumption [25], [51].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it should be noted that we consider only one rate term for glutamine utilization for both protein and DNA synthesis. In this way the glutamine pool (compartment A in Fig.1) is subdivided into three pools that sustain the STORE compartment (p 11 ), energy production (p 22 ) and biosynthesis (p 33 ) and where p 11 and p 22 are dynamically interconnected through the ATP sensor (see also [6] for details).…”
Section: Protein and Dna Synthesismentioning
confidence: 99%
“…Simulated cell in the model transiently produce more ATP in low glucose media because of the ATP sensor that has been fully described in our previous paper. The ATP sensor was introduced to tune the rates r 3 , p 22 and p 11 shown in Fig.1 and was meant to model phenomenologically both the Pasteur and the Crabtree effects [6]. At low glucose concentrations, the ATP production rate falls below the standard assumed value (ATP_St, [6]) and turns on the ATP sensor.…”
Section: Simulations Carried Out Under Abnormal Growth Conditions: Prmentioning
confidence: 99%